Theoretical-computational characterization of the temperature-dependent folding thermodynamics of a β-hairpin peptide - Daidone, Isabella; Zanetti-Polzi, Laura; Thukral, Lipi; Alekozai, Emal M.; Amadei, Andrea (Chemical physics letters, 2016)
A theoretical-computational approach is presented to characterize the temperature-dependent thermodynamics of protein folding. Making use of the Quasi-Gaussian Entropy (QGE) theory and temperature exchanged molecular dynamics (TREMD) simulations, a complete picture of the folding thermodynamics can be obtained. The strategy is applied to analyze the folding thermodynamics of a β-hairpin peptide, Peptide 1, the folding process of which was experimentally characterized by means of infrared spectroscopy. The results provided by the approach here presented very well reproduce the experimental results, showing that the methodology can be successfully utilized to investigate the thermodynamics of folding processes in a wide temperature range.
Gesehen am 06.05.2020